BMP‐2 Signaling and Mechanotransduction Synergize to Drive Osteogenic Differentiation via YAP/TAZ. Issue 15 (16th June 2020) - Wei, Qiang; Holle, Andrew; Li, Jie; Posa, Francesca; Biagioni, Francesca; Croci, Ottavio; Benk, Amelie S.; Young, Jennifer; Noureddine, Fatima; Deng, Jie; Zhang, Man; Inman, Gareth J.; et al.
Abstract: Growth factors and mechanical cues synergistically affect cellular functions, triggering a variety of signaling pathways. The molecular levels of such cooperative interactions are not fully understood. Due to its role in osteogenesis, the growth factor bone morphogenetic protein 2 (BMP‐2) is of tremendous interest for bone regenerative medicine, osteoporosis therapeutics, and beyond. Here, contribution of BMP‐2 signaling and extracellular mechanical cues to the osteogenic commitment of C2C12 cells is investigated. It is revealed that these two distinct pathways are integrated at the transcriptional level to provide multifactorial control of cell differentiation. The activation of osteogenic genes requires the cooperation of BMP‐2 pathway‐associated Smad1/5/8 heteromeric complexes and mechanosensitive YAP/TAZ translocation. It is further demonstrated that the Smad complexes remain bound onto and active on target genes, even after BMP‐2 removal, suggesting that they act as a "molecular memory unit." Thus, synergistic stimulation with BMP‐2 and mechanical cues drives osteogenic differentiation in a programmable fashion. Abstract : Bone morphogenetic protein 2 (BMP‐2) signaling and mechanotransduction pathways are integrated at the transcriptional level to provide multifactorial control of cell differentiation. The activation of osteogenic genes requires the cooperation of BMP‐2 pathway‐associated Smad1/5/8 heteromeric complexes and mechanosensitive YAP/TAZ translocation. The Smad complexes remain bound onto and active on target genes, even after BMP‐2 removal, suggesting that they act as a "molecular memory unit."